(untitled) (Journal of NELTA, 2021)
With an increasingly diverse student population in the classroom, it is imperative that teachers feel confident about their ability to teach reading to children who have varied reading proficiency to read. This study has explored in-service teacher beliefs on learner diﬀerences in reading instruction in school classrooms that instigated teacher strategies in meeting learner needs. Data were collected from classroom observation and interviews from two experienced teachers. Transcripts and field notes were coded and analyzed thematically. The result indicated that the teachers had high expectations for their students, however, they lacked suﬃcient skills to diﬀerentiate reading instruction to address the needs of students on a regular basis. Classroom instruction was mostly dominated by lecture methods and the materials and activities were limited to textbooks. The teachers saw reading diﬀerences as a classroom reality, recognized students reading diﬀerences in the classroom, and felt the need to grow every learning potential in reading. Some of the teaching strategies that aligned with diﬀerentiated reading instruction were: flexible grouping, library lesson and choice in reading, diﬀerentiated support, multisensory presentation of lessons, extension activities for high achieving readers, activating background knowledge and making connection, peer tutoring, exploratory activities, curriculum compacting, ongoing assessment and feedback, diﬀerentiated questioning, diﬀerentiated assignment, repeated instruction, and using technology.